THE COMPETITIVE ADVANTAGE OF PT. PHM DURING COVID-19 PANDEMIC: A CASE STUDY ON AN INDUSTRIAL SUPPLIER FAMILY BUSINESS - Michael Pratomo S.M.; Jacob Donald Tan (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2022)
PT. PHM is an industrial supplier business that distributes most of their products to state-owned enterprises in Palembang, South Sumatera. This family business has been operational for 30 years and during the COVID-19 pandemic, even though the trading industry has decreased significantly, this company can still survive and even perform profitably. The company is currently still facing the tight competition in the market especially during pandemic. Therefore, the researchers investigated factors that contribute to PT. PHM’s competitive advantage during the pandemic by applying single instrumental case study that involves interviews, observations, and field notes, and approaching 2 owners, 4 employees, and 4 customers for this study. The latent variables that emerged such as Integrity, Diligence, Product Knowledge, Problem Solving Skill, Competitive Price, Employees’ Performance, Owners-Employees Relationship, Product Precision, Prompt Communication Response, Certified Quality were constructed into a mini-model theory. Hence, this could guide the family business in enhancing its competitive advantage during and even beyond the pandemic.